Kepastian Hukum terhadap Perbuatan Melawan Hukum dalam Sengketa Kepemilikan Tanah - Ramadhan, Ahsanul Rizqi; Miharja, Marjana (Neolectura, 2025)
Land issues and conflicts are increasingly becoming a serious concern in various regions in Indonesia. As a country with a large population and limited land, land has a very important value for various parties, including individuals, groups, governments, and companies. One problem that often arises is the issuance of Land Ownership Certificates (SHM) that are carried out illegally or contrary to applicable legal provisions. The formulation of the problem in this study is how the perpetrators are held accountable for unlawful acts related to land ownership or control and what legal considerations are used by judges in deciding cases of unlawful acts related to land disputes in Civil Lawsuit Decision Number 1/Pdt.G/2020/PN Pbm. The research method used is normative juridical. The results of the study are that land ownership disputes often give rise to complex legal issues and can give rise to civil, criminal, or administrative liability, depending on the form of violation and its legal consequences. In civil law, the perpetrator of an unlawful act is obliged to compensate for the losses incurred, while in the criminal realm, violations such as land grabbing, document falsification, and fraud can be subject to criminal sanctions in accordance with the Criminal Code (KUHP). Administrative actions, such as the cancellation of certificates by the National Land Agency (BPN), can also be taken. In a land dispute decision in Prabumulih City, the Court rejected all of Defendant III's exceptions and granted part of the Plaintiff's lawsuit. The panel of judges stated that the 960 m² of land legally belonged to the Plaintiff, and Defendant I's actions in selling the land to Defendant II and Defendant III's issuance of a Certificate of Ownership without the Plaintiff's consent constituted an unlawful act. Consequently, the sale and purchase agreement and certificate were declared invalid and not legally binding. Defendants I and II were sentenced to pay Rp. 50,000 per day in damages jointly and severally if they failed to implement the decision, and were required to pay court costs of Rp. 2,621,000. The Plaintiff's lawsuit other than and beyond that was rejected.